Pengaruh Kapasitas Anaerobik terhadap Beberapa Keterampilan, Variabel Mental dan Fungsional di Kalangan Pemain - Ali Mohammed Jaber (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. The study aimed to identify the level of anerobic phosphagens and lactic ability of football and futsal players, and to identify the level of some basic skills, mental, and functional variables of the players. As well as identifying the differences of some mental and functional variables between football versus futsal players for phosphagen and lactic effort. Materials and methods. The researcher used the experimental method, the research sample consisted participating players of the Iraqi Premier League of football (8) players, and futsal (8) players, n= 16 players, tests and measurements were used for the research variables, the researcher assumes that there are differences in the level of phosphagen and lactic oxygen capacity between football and futsal players. Results.  Results showed significance differences in Phosphagens capacity between football and futsal players,  there are no differences between football and futsal players in basic skills, there are no differences between football and futsal players in mental abilities, there are differences between football and futsal players in mental abilities with lactic effort. Conclusion. The researcher concluded the superiority of futsal players in the anerobic capacity, there is no difference in basic skills between football and futsal players with phosphagen and lactic effort, there are no differences in variables Physiological phosphagen effort, there are differences in favor of football players in pulse, respiratory rate, and heart energy, futsal players excelled in concentration and distribution of attention.